Chlorination Operations at Jerritt Canyon, Nevada - D. S. Barr (The Minerals, Metals and Materials Society, 1987)
The Freeport McMoRan chlorination circuit is comprised of four related processes: ore chlorination, gas scrubbing, chlorine supply and excess hypochlorite removal ("hypo kill"). Each of these processes are described, and related to the pertinent mineralogic components in the carbonaceous ore feed to the plant. The chlorination system in use at Jerritt Canyon to passivate forms of preg-robbing organic carbon has proven to be a cost effective and efficient means to recover gold from low sulfide carbonaceous refractory ores, where gold may not be specifically associated with either the sulfides or the carbon.